How Consumers in Indonesia Are Protected Fairly? - Wibowo, Dwi Edi (Indonesian Journal of Advocacy and Legal Services, 2020)
The progress of the times accompanied by increasingly sophisticated technology, opens new opportunities in the national economic development sector. New opportunities, namely business opportunities, are expected to encourage the macroeconomic sector to become more advanced so as to be able to improve the level of welfare of the people of Indonesia, with an increase in business opportunities in the modern world, so goods and services as the main commodity will certainly develop as well. However, goods and services as an element in these economic transactions open up opportunities for the emergence of possible losses suffered by consumers as part of fraud, negligence, or intentional business actors. This condition raises an understanding of the need for protection of consumers as parties who are often harmed by the actions of these 'naughty' business actors. In fact, an institution has been formed which aims to bring consumers to defend their rights as consumers, namely the Indonesian Consumers Foundation, but consumers are still reluctant to go through the judiciary for themselves so that they are more resigned to what they experience.